Hasil Belajar Siswa Pada Konsep Energi Dan Kegunaannya Menggunakan Model Think Pair And Share Bervariasi Media Realita Di Kelas IV SDN Gudang Tengah Sungai Tabuk Kab. Banjar - Nor Lila Sari; Rofi Shafwan; Ayu Anindia Hizraini (Journal on Education, 2024)
This study aims to describe the implementation and improvement of the results of the science learning for Grade 4 students using cooperative learning model Think Pair and Share varying media reality energy material and its use of energy. The type of research is the Classroom Action Research. PTK'S step consisting of: planning, performing, observation, and reflection. The Subjects were students in grade 4B SDN Gudang Tengah Sungai Tabuk Kabupaten Banjar academic year 2013/2014 in the second semester. This observational Result is activity teacher to utilize TPS'S learning model varies realita's media experience step-up of I. cycle 66,25% and cycles II. 85%, student activity increases of I. cycle 63,26% as 85,43% on cycle II., meanwhile student studying result also experience step-up which is of I. cycle 59% as 80,11% on cycle II.